2017
DOI: 10.24193/tras.2017.0005
|View full text |Cite
|
Sign up to set email alerts
|

Facebook as a Dialogic Strategic Tool for European Local Governments

Abstract: The main aim of this study is to analyze the extent to which local governments in the EU apply dialogic strategies in their Facebook profi les in order to establish and enhance relations with society, and then to examine the impact of certain factors on the implementation of these dialogic strategies. A descriptive analysis is made of the implementation of the dialogic communication theory in relation to the use of Facebook, and this is followed by an explanatory analysis of factors leading local governments t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Besides, it is concluded that they did not make use of the advantages of social media platforms to build stronger dialogues with their stakeholders particularly during the pandemic days when most of their stakeholders were expected to stay home, work from home and also to search for new entrepreneurship, research and development opportunities which technoparks could offer. As for each principle of dialogic communication, it is clear that Instagram accounts were preferred mostly for disseminating information (as also found in the studies of Silkü-Bilgilier and Kocaömer in 2020, and Arslan in 2019), while Facebook accounts were used mostly for attracting audiences for their return visits (which results in deficiency in dialogic communication as discovered by Haro-de-Rosario, Sáez-Martín, & del Mar Gálvez-Rodríguez, 2017;Saxton & Waters, 2014;Capriotti & Losada-Díaz, 2018;Oltarzhevskyi et al, 2018;Shin et al, 2015 in their studies), and the technoparks mostly used features of Twitter that made it possible to keep audiences on the platform (which shows important similarities with the major findings of prior research such as Rybalko & Seltzer, Connectist: Istanbul University Journal of Communication Sciences, 2021, 60, 1-26 2010; Kemna, 2013;del Mar Gálvez-Rodríguez et al, 2016;Beverly, 2013;Shin et al, 2015;Yue et al, 2019). This may signal the different social media strategies of technoparks for each platform, which, if that is the case, demonstrates that there is no consistency among those strategies.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Besides, it is concluded that they did not make use of the advantages of social media platforms to build stronger dialogues with their stakeholders particularly during the pandemic days when most of their stakeholders were expected to stay home, work from home and also to search for new entrepreneurship, research and development opportunities which technoparks could offer. As for each principle of dialogic communication, it is clear that Instagram accounts were preferred mostly for disseminating information (as also found in the studies of Silkü-Bilgilier and Kocaömer in 2020, and Arslan in 2019), while Facebook accounts were used mostly for attracting audiences for their return visits (which results in deficiency in dialogic communication as discovered by Haro-de-Rosario, Sáez-Martín, & del Mar Gálvez-Rodríguez, 2017;Saxton & Waters, 2014;Capriotti & Losada-Díaz, 2018;Oltarzhevskyi et al, 2018;Shin et al, 2015 in their studies), and the technoparks mostly used features of Twitter that made it possible to keep audiences on the platform (which shows important similarities with the major findings of prior research such as Rybalko & Seltzer, Connectist: Istanbul University Journal of Communication Sciences, 2021, 60, 1-26 2010; Kemna, 2013;del Mar Gálvez-Rodríguez et al, 2016;Beverly, 2013;Shin et al, 2015;Yue et al, 2019). This may signal the different social media strategies of technoparks for each platform, which, if that is the case, demonstrates that there is no consistency among those strategies.…”
Section: Discussionmentioning
confidence: 83%
“…As one of the leading social networking platforms, Facebook offers its users to share information, create and sustain constant interaction (such as conversation, negotiation, discussion, exchange, and so on), and cultivate dynamic relationships with their key audiences, which in turn gives way to developing strong dialogue, through its powerful dialogic functions (Capriotti & Losada-Díaz, 2018) such as comments, reactions, polls, and events and the like. Unlike some prior research (Kim et al, 2014b), more recent studies (Haro-de-Rosario, Sáez-Martín, & del Mar Gálvez-Rodríguez, 2017;Saxton & Waters, 2014;Capriotti & Losada-Díaz, 2018;Oltarzhevskyi et al, 2018;Shin et al, 2015) assert that many organizations manage their Facebook accounts only for disseminating information instead of establishing a two-way dialogue.…”
Section: Technoparks As Dynamically Powerful Technology Development Zones (Sanayi Vementioning
confidence: 92%
See 1 more Smart Citation
“…The existing advertising saturation affects the effectiveness of campaigns [20]. For this reason, companies, instead of investing in a massive marketing, should focus on building relationships with customers and making personalized messages [12]. Regarding to this and because of the Internet, public relations and the way organizations involve their publics has changed considerably in recent years [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, we cannot forget that social media is based on dialogue, so organizations must pay attention to this situation with the purpose of participating on it and in dialoguing with its clients [12]. Therefore, it is common for large companies to use the means of social communication, such as Facebook [21].…”
Section: Introductionmentioning
confidence: 99%